Footprints of the sun: memory of UV and light stress in plants - Müller-Xing, Ralf; Xing, Qian; Goodrich, Justin (Frontiers in Plant Science, 2014)
Sunlight provides the necessary energy for plant growth via photosynthesis but high light and particular its integral ultraviolet (UV) part causes stress potentially leading to serious damage to DNA, proteins and other cellular components. Plants show adaptation to environmental stresses, sometimes referred to as “plant memory”. There is growing evidence that plants memorize exposure to biotic or abiotic stresses by epigenetic mechanisms at the cellular level. UV target genes such as CHALCONE SYNTHASE (CHS) response immediately to UV treatment and studies of the recently identified UV-B receptor UV RESISTANCE LOCUS 8 (UVR8) confirm the expedite nature of UV signalling. Considering these findings, an UV memory seems redundant. However, several lines of evidence suggest that plants may develop an epigenetic memory of UV and light stress, but in comparison to other abiotic stresses there has been relatively little investigation. Here we summarize the state of knowledge about acclimation and adaptation of plants to UV light and discuss the possibility of chromatin based epigenetic memory.